AHP-TOPSIS for analyzing job performance with factor evaluation system and process mining - Gabriel Sophia; Riyanarto Sarno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Job performance is a type of assessments which refers to scalable actions, behaviour and outcomes that employees engage in or bring out linked with and contribute to organizational goals.This research employed the Factor Evaluation System (FES) method to analyze the job performance due to the common usage of the method. In analyzing employees, FES consists of nine factors; however, those nine factors are considered to be insufficient. Hence, the researchers used the process mining method to improve FES. Process mining analyzes job performance in details. The steps taken in process mining consist of time stamp, case, activity, and resources of employee. This means that the method can be continuously used, since the researcher provides weight for each factor. The weight of each factor is obtained from Analytic Hierarchy Process-Technique for Order Preference by Similarity to Ideal Solution. The result shows that FES with process mining are good for job performance but AHP-TOPSIS is considered to be incompatible for usage compared to the real work because the priority of the FES factors from the method is inconsistent with the priority factor made by manager of the warehouse officer.